2022
DOI: 10.1021/acs.joc.2c01272
|View full text |Cite
|
Sign up to set email alerts
|

Solvent Dependent Competitive Mechanisms for the Ugi Multicomponent Reaction: A Joint Theoretical and Experimental Study in the α-Acyl Aminocarboxamides vs α-Amino Amidines Formation

Abstract: A synthetic protocol for the preparation of α-acyl aminocarboxamides and α-amino amidines is proposed. The selectivity toward each of these two possible products was tuned by simple modifications of the reaction conditions. A broad scope is presented, allowing access to the desired products in up to 87% (Ugi adduct) and 93% (α-amino amidine). Theoretical calculations were carried out, and the analysis led to the proposal of a new mechanistic pathway for the Ugi reaction, in which methanol acts not only as the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…To address the limitation of low yield encountered in the previous method of lipid generation using the 3-CR-Ugi reaction, we conducted an investigation into various catalysts, including p -toluenesulfonic acid, phosphoric acid, boric acid, and phenylphosphinic acid for boosting the reaction efficiency ( 27 31 ). Remarkably, phenylphosphinic acid (20% mol) emerged as the most effective catalyst, increasing the reaction yield from 10 to 70% ( SI Appendix , Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To address the limitation of low yield encountered in the previous method of lipid generation using the 3-CR-Ugi reaction, we conducted an investigation into various catalysts, including p -toluenesulfonic acid, phosphoric acid, boric acid, and phenylphosphinic acid for boosting the reaction efficiency ( 27 31 ). Remarkably, phenylphosphinic acid (20% mol) emerged as the most effective catalyst, increasing the reaction yield from 10 to 70% ( SI Appendix , Fig.…”
Section: Resultsmentioning
confidence: 99%
“…As an illustration, we have recently demonstrated that a simple change in solvent, such as using methanol, can modulate the mechanism of the Ugi 4-component MCR, directing it towards an alternative catalytic cycle. 16…”
Section: Introductionmentioning
confidence: 99%
“…The isocyanide based multicomponent reactions (I-MCRs), especially Ugi four-component reactions, have played a vital role in organic and medicinal chemistry due to their efficient construction of small-molecule libraries in a mild one-pot fashion. , The Ugi-azide reactions have also provided a powerful method for synthesis of 1,5-disubstituted tetrazoles, as the carboxylic acid component is changed to hydrazoic acid (produced in situ from NaN 3 or TMS-N 3 ). In recent years, the sequence of Ugi reaction and other organic reactions has been successfully applied in the synthesis of many heterocyclic compounds. For example, the tandem post-Ugi cyclization and Gold­(I)-catalyzed regioselective annulation were utilized in the preparation of densely functionalized pyrrolo­[1,2- a ]­pyrazine-3,6­(2 H ,4 H )-diones in good to excellent yields . Diverse benzazepinoindoles were assembled in a step-economical, chemo- and regioselective fashion by an Ugi/gold-catalyzed alkyne hydroarylation/Michael addition sequence .…”
mentioning
confidence: 99%